K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

Sure, let's solve the equation step by step:

Given Equation:

2⋅3x−1+5⋅3x−3=18632⋅3x−1+5⋅3x−3=1863

Step 1: Combine Like Terms

First, combine the terms with 3x3x and the constant terms separately:

(2⋅3x+5⋅3x)+(−1−3)=1863(2⋅3x+5⋅3x)+(−1−3)=1863 7⋅3x−4=18637⋅3x−4=1863

Step 2: Isolate the Exponential Term

Add 4 to both sides of the equation to isolate the term with 3x3x:

7⋅3x=1863+47⋅3x=1863+4 7⋅3x=18677⋅3x=1867

Step 3: Solve for 3x3x

Divide both sides by 7 to solve for 3x3x:

3x=186773x=71867 3x=266.7142857(approximately)3x=266.7142857(approximately)

Step 4: Solve for xx Using Logarithms

To solve for xx, take the logarithm base 3 of both sides:

x=log⁡3(18677)x=log3(71867)

Using the change of base formula or a calculator:

x=ln⁡(18677)ln⁡(3)≈ln⁡(266.7142857)ln⁡(3)≈5.8891.0986≈5.36x=ln(3)ln(71867)≈ln(3)ln(266.7142857)≈1.09865.889≈5.36

Final Answer:

x≈5.36x≈5.36

\(2\cdot3^{x-1}+5\cdot3^{x-3}=1863\)

=>\(2\cdot3^x\cdot\dfrac{1}{3}+5\cdot3^x\cdot\dfrac{1}{27}=1863\)

=>\(3^x\left(\dfrac{2}{3}+\dfrac{5}{27}\right)=1863\)

=>\(3^x\cdot\dfrac{23}{27}=1863\)

=>\(3^x=1863:\dfrac{23}{27}=2187=3^7\)

=>x=7

a: =>x-2/5=3/4:1/3=3/4*3=9/4

=>x=9/4+2/5=45/20+8/20=53/20

b: =>x-2/3=7/3:4/5=7/3*5/4=35/12

=>x=35/12+2/3=43/12

c: 1/3(x-2/5)=4/5

=>x-2/5=4/5*3=12/5

=>x=12/5+2/5=14/5

d: =>2/3x-1/3-1/4x+1/10=7/3

=>5/12x-7/30=7/3

=>5/12x=7/3+7/30=77/30

=>x=77/30:5/12=154/25

e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)

=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)

=>x=19/7:23/28=76/23

f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5

=>13/12x=1/5+3/2+4/3+5/4=257/60

=>x=257/65

i: =>x^2-2/5x-x^2-2x+11/4=4/3

=>-12/5x=4/3-11/4=-17/12

=>x=17/12:12/5=85/144

15 tháng 2 2020
https://i.imgur.com/zKeoHqB.jpg
2 tháng 3 2021

Bài dài quá, lần sau chia nhỏ câu hỏi nhé!!!!!

12 tháng 9 2021

đúng vậy

AH
Akai Haruma
Giáo viên
2 tháng 3 2021

Bạn cần viết đề bài bằng công thức toán để được hỗ trợ tốt hơn. 

4 tháng 3 2021

x^2+2x-3/3+2x/4=x^2/3

28 tháng 4 2018

a) \(\left(3x-1\right).\left(\frac{-1}{2}x+5\right)=0\)

\(\Rightarrow3x-1=0\Rightarrow3x=1\Rightarrow x=\frac{1}{3}\)

\(\frac{-1}{2}x+5=0\Rightarrow\frac{-1}{2}x=-5\Rightarrow x=10\)

b) \(3\left(x-\frac{1}{2}\right)-5\left(x+\frac{3}{5}\right)=x+\frac{1}{5}\)

\(3x-\frac{3}{2}-5x-3=x+\frac{1}{5}\)

\(\Rightarrow3x-5x-x=\frac{1}{5}+\frac{3}{2}+3\)

\(-3x=\frac{47}{10}\)

\(x=\frac{-47}{30}\)

c) \(-5.\left(x+\frac{1}{5}\right)-\frac{1}{2}\left(x-\frac{2}{3}\right)=\frac{3}{2}x-\frac{5}{6}\)

\(-5x-1-\frac{1}{2}x+\frac{1}{3}=\frac{3}{2}x-\frac{5}{6}\)

\(-5x-\frac{1}{2}x-\frac{3}{2}x=\frac{-5}{6}+1-\frac{1}{3}\)

\(-7x=\frac{-1}{6}\)

\(x=\frac{1}{42}\)

d) \(3.\left(3x-\frac{1}{2}\right)^3+\frac{1}{9}=0\)

\(3.\left(3x-\frac{1}{2}\right)^3=\frac{-1}{9}\)

\(\left(3x-\frac{1}{2}\right)^3=\frac{-1}{27}\)

\(\left(3x-\frac{1}{2}\right)^3=\left(\frac{-1}{3}\right)^3\)

\(\Rightarrow3x-\frac{1}{2}=\frac{-1}{3}\)

\(3x=\frac{1}{6}\)

\(x=\frac{1}{18}\)

Học tốt nhé bn!
 

11 tháng 8 2021

x = \(\frac{1}{18}\)nha

9 tháng 1 2021

Câu 1 : 

a, \(\frac{3\left(2x+1\right)}{4}-\frac{5x+3}{6}=\frac{2x-1}{3}-\frac{3-x}{4}\)

\(\Leftrightarrow\frac{6x+3}{4}+\frac{3-x}{4}=\frac{2x-1}{3}+\frac{5x+3}{6}\)

\(\Leftrightarrow\frac{5x+6}{4}=\frac{9x+1}{6}\Leftrightarrow\frac{30x+36}{24}=\frac{36x+4}{24}\)

Khử mẫu : \(30x+36=36x+4\Leftrightarrow-6x=-32\Leftrightarrow x=\frac{32}{6}=\frac{16}{3}\)

tương tự 

16 tháng 5 2021

\(\frac{19}{4}-\frac{2\left(3x-5\right)}{5}=\frac{3-2x}{10}-\frac{3x-1}{4}\)

\(< =>\frac{19.5}{20}-\frac{8\left(3x-5\right)}{20}=\frac{2\left(3-2x\right)}{20}-\frac{5\left(3x-1\right)}{20}\)

\(< =>95-24x+40=6-4x-15x+5\)

\(< =>-24x+135=-19x+11\)

\(< =>5x=135-11=124\)

\(< =>x=\frac{124}{5}\)

AH
Akai Haruma
Giáo viên
11 tháng 8 2021

1.

$(x-2)(x-5)=(x-3)(x-4)$

$\Leftrightarrow x^2-7x+10=x^2-7x+12$
$\Leftrightarrow 10=12$ (vô lý)

Vậy pt vô nghiệm.

2.

$(x-7)(x+7)+x^2-2=2(x^2+5)$

$\Leftrightarrow x^2-49+x^2-2=2x^2+10$
$\Leftrightarrow 2x^2-51=2x^2+10$

$\Leftrightarrow -51=10$ (vô lý)

Vậy pt vô nghiệm.

AH
Akai Haruma
Giáo viên
11 tháng 8 2021

3.

$(x-1)^2+(x+3)^2=2(x-2)(x+2)$
$\Leftrightarrow (x^2-2x+1)+(x^2+6x+9)=2(x^2-4)$
$\Leftrightarrow 2x^2+4x+10=2x^2-8$

$\Leftrightarrow 4x+10=-8$

$\Leftrightarrow 4x=-18$

$\Leftrightarrow x=-4,5$

4.

$(x+1)^2=(x+3)(x-2)$

$\Leftrightarrow x^2+2x+1=x^2+x-6$

$\Leftrightarrow x=-7$ 

 

2 tháng 4 2020

1) \(\left|x+\frac{4}{5}\right|+\frac{7}{5}=\frac{3}{5}\)

\(\Rightarrow\left|x+\frac{4}{5}\right|=\frac{3}{5}-\frac{7}{5}\)

\(\Rightarrow\left|x+\frac{4}{5}\right|=\frac{-4}{5}\)

\(x+\frac{4}{5}=\pm\frac{4}{5}\)

\(TH1:x+\frac{4}{5}=\frac{4}{5}\)

\(\Rightarrow x=\frac{4}{5}-\frac{4}{5}=0\)

\(TH2:x+\frac{4}{5}=\frac{-4}{5}\)

\(\Rightarrow x=\frac{-4}{5}-\frac{4}{5}=\frac{-8}{5}\)

Vậy x ∈ {0; \(\frac{-8}{5}\)}

2 tháng 4 2020

Hỏi đáp ToánHỏi đáp ToánHai câu cuối khó nhìn nên ko giải